Reflections from an Adjunct: How the Scholarship of Teaching and Learning Empowers the Part-Time Instructor - Maria C. Durso, MA (Park University, 2011)
In this reflective piece, an adjunct instructor narrates her experience with institutional efforts to encourage faculty to become better instructors through exposure to and engagement in the Scholarship of Teaching and Learning (SoTL). Institutions of higher education can find it difficult to draw faculty out of their instructional status quo. Of particular concern are part-time instructors who, typically less connected to the institution than full-time professors, may struggle to find the resources to improve instruction, even if such resources are desired. As a case in point, this piece demonstrates that early, consistent, persistent, quality exposure to SoTL, combined with individual commitment, does yield concrete improvement in teaching and learning.